Estimating Policy Position of the Candidates in the 2017 Gubernatorial Election in Jakarta - Gunawan, Aditya Batara (Jurnal Politik Indonesia: Indonesian Political Science Review, 2018)
This study attempts to understand the policy position of candidates in the 2017 gubernatorial election in Jakarta. This study utilized the concept of â€œpolicy positionâ€ â€“which has been widely discussed in the electoral studiesâ€” in order to distinguish policy orientation of political parties/candidates, and explaining voter preferences in electoral competition. In so doing, this study introduces the application of the quantitative text analysis method with the Wordfish model towards electoral platform of candidates in the 2017 gubernatorial election in Jakarta to estimate their policy positions. The model calculates word distribution and word frequency in the electoral platforms by using simple Poisson process of statistical distribution. The process results in two key findings: two pairs of candidates (Agus-Sylvy and Anies-Sandi) indicated closer policy distance in the policy space, and socioeconomic issues emerged as central feature in the political rhetoric across the candidates. These findings are further confirmed by the observation of the voter preference distributions and the public statements of each candidate during the election.